Information and communication technologies for ageing well and e-Health : second International Conference, ICT4AWE 2016, Rome, Italy, April 21-22, 2016, Revised selected papers /: second International Conference, ICT4AWE 2016, Rome, Italy, April 21-22, 2016, Revised selected papers. (2017) - Unknown
No abstract available